The Urgency of Increasing National Cyber Security as an Effort to Protect Personal Data - Febriansyah, Febriansyah (Social Sciences Insights Journal, 2023)
One form of Cybercrime is social media hacking and piracy which leads to personal data breaches. One of the cases that went viral in 2022 was that carried out by Bjorka. Bjorka once claimed to have 26 million browsing histories of Indihome customers, even confidential state documents. This can happen of course because of weak cyber security in Indonesia. This research aims to determine the legal construction of resolving hacking cases against personal data according to Indonesian laws and regulations, and how the government should make efforts to improve national cyber security. The research method used is normative juridical. The research results show that the ITE Law provides regulations that are still too general regarding the criminal act of hacking personal data. After the Personal Data Protection Law was introduced, Indonesia now has special regulations for this. However, to improve national cyber security, Indonesia must be more involved in international conventions regarding cybercrime.